Subjective memory complaints in young people; their relationship with objective cognitive performance and the role of neuroticism - Crespo-Sanmiguel, Isabel; Zapater-Fajarí, Mariola; Garrido-Chaves, Ruth; Hidalgo, Vanesa; Salvador, Alicia (Anales de Psicología / Annals of Psychology, 2024)
Perceptions of recurrent forgetfulness or episodes of distraction in daily life are referred to as subjective memory complaints (SMCs). Their nature has been extensively studied in older adults, but their significance and relationship with neurocognitive performance have not been fully addressed in younger adults. Some psychological traits have been suggested as possible moderators of the association between objective and subjective memory performance. The first aim of this study was to analyze the correspondence between the objective and subjective perception of memory failures in young people. Second, we studied whether the psychological trait of neuroticism could be influencing this relationship. To do this, we measured SMCs, different cognitive domains (episodic and working memory and executive functions), and neuroticism in 80 young men and women. Results showed that only immediate episodic memory was statistically related to SMCs. Interestingly, the negative relationships between objective and subjective memory performance only appeared in participants with higher neuroticism. Thus, memory complaints reported by young people could reflect poorer immediate episodic memory performance, whereas neuroticism would play a main role in the association between memory deficits and SMCs. This study provides data that can help to better understand SMCs in young people.